Modos de aplicação e reaplicação de calcário nas culturas de milho e soja em plantio direto: Efeito residual - Oliveira, Wandemberg Assis Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Studies involving liming and tillage are still needed to further recommendations of this practice in many different soils and climatic conditions where this system is used for cultivation. In this context, this study was conducted at experimental area UNESP - Ilha Solteira Campus, located in Selvíria county, Mato Grosso do Sul State, Brazil, with the objective to evaluate the effect of doses, methods of application and reapplication of limestone in corn and soybean crops in no-tillage system. In crop year 1999/00, began an experiment with modes of limestone application and cover crops, using the completely randomized design with treatments arranged in a factorial 4 x 2, or 4 modes of limestone application (incorporated, surface, surface before cover crop management and without liming ), 2 cover crops (millet and oats) before corn or soybeans crops. In treatments where there was limestone application, the dose used was 1,235 kg ha -1 with PRNT 91%. During the growing season 2002/03, wasn't longer considered as cover crops treatment and a new dose (769 kg ha -1 ) surface was reapplied in the presence or absence of scarification. In the treatment with limestone application on surface before cover crops management, it was applied 0.5, 1.0, 1.5, 2.0 and 2.5 times respectively the calculated dose for the other treatments. In the years 2003/04 and 2004/05 was evaluated the residual effect of the treatments. In crop year 2005/06, were kept modes of application of limestone, used in the experiment, and there was reapplication of two different types of limestone (C1 - PRNT 91% and C2 - PRNT 81.9%) in doses of 841.2 and 900.6 kg ha -1 respectively and on treatment CM doses limestone C1 were compared again. In 2006/07 and 2007/08, remained the treatments used in the previous year, thus attempting to evaluate the residual effect of the treatments. In 2008/ 09, before the sowing of corn and soybeans, was reapplied a new dose of limestone with ...

Estudos que envolvam calagem e sistema plantio direto ainda são necessários para melhor embasar as recomendações desta prática nos mais diferentes solos e condições climáticas onde se utiliza deste sistema de cultivo. Neste contexto, o presente trabalho foi desenvolvido na área experimental da FEPE/UNESP - Campus de Ilha Solteira, localizada no município de Selvíria - MS, com o objetivo de avaliar o efeito residual de doses, modos de aplicação e reaplicação de calcário nas culturas de milho e soja em sistema plantio direto. No ano agrícola 1999/00, iniciou-se um experimento com modos de aplicação de calcário e culturas de cobertura, utilizando-se o delineamento experimental inteiramente casualizado, com os tratamentos dispostos em um esquema fatorial 4 x 2, ou seja, 4 modos de aplicação de calcário (incorporado, superfície, em superfície antes manejo das culturas de cobertura e sem aplicação de calcário) e 2 culturas de cobertura do solo (nilheto e aveia) antecedendo as culturas produtoras de grãos (milho e soja). Nos tratamentos onde houve aplicação de calcário, utilizou-se a dose de 1235 kg ha -1, com PRNT de 91%. No ano agrícola 2002/03, não mais considerou-se as culturas de cobertura como tratamento e uma nova dose (769 kg ha -1 ) foi reaplicada em superfície, na presença ou ausência de escarificação. No tratamento com aplicação de calcário em superfície antes do manejo das culturas de cobertura (CM), aplicou-se em superfície, 0,5; 1,0; 1,5; 2,0 e 2,5 vezes, respectivamente a dose calculada para os demais tratamentos. Nos anos agrícolas 2003/04 e 2004/05 avaliou-se o efeito residual dos tratamentos. No ano agrícola de 2005/06, foram mantidos os modos de aplicação de calcário, utilizados na instalação do experimento e houve reaplicação de dois diferentes tipos de calcário (C1 - PRNT de 91% e C2 - PRNT de 81,9%) nas doses de 841,2 e 900,6 kg ha -1 respectivamente e no tratamento CM,...
Keywords: Milho - Cultivo; Soja - Cultivo; Plantio direto; Calagem dos solos; Cerrados